Boundaries as tools for sustainable water management - Tomaz Dentinho; Vasco Silva (European Regional Science Association (ERSA), 2005)
Accross river basins water can have different types of values according not only to its production costs but also due to changes in the willingness to pay across the territory. The generalized view that integrated water management must be made through a centralised mechanism does not consider those facts and often assumes that command and control policies are the only tool available and effective. Therefore the functioning of river basins tend to be symplified with dams and the reserach agenda has been directed to design major models with powerful decision support systems for one coordinator body to decide. Nevertheless the effects of these centralised and controled systems has not been able to address the impredictability of human and ecosystem behaviour. The hypothesis we would like to test is that boundaries and negotiation between boundaries can be good tools for sustainable water management. First we review the literature on cases of basins' manegement trying to discuss the relation between boundaries. Then we develop a formal model with upstream and downstream regions and try to understand in what conditions boundaries can be good for sustainable water management. Finaly we try to introduce the concept of boundaries in an applied model for a particular river basin and simulate the solutions for a centralised planning body and for a descentralised negotiation system.
Keywords: 330